Early Endosomal Trafficking Component BEN2/VPS45 Plays a Crucial Role in Internal Tissues in Regulating Root Growth and Meristem Size in Arabidopsis - Matsuura, Yuki; Fukasawa, Narumi; Ogita, Kosuke; Sasabe, Michiko; Kakimoto, Tatsuo; Tanaka, Hirokazu (Frontiers in Plant Science, 2020)
Polar auxin transport is involved in multiple aspects of plant development, including root growth, lateral root branching, embryogenesis and vasculature development. PIN-FORMED (PIN) auxin efflux proteins exhibit asymmetric distribution at the plasma membrane (PM) and collectively play pivotal roles in generating local auxin accumulation, which underlies various auxin-dependent developmental processes. In previous research, it has been revealed that endosomal trafficking components BEN1/BIG5 (ARF GEF) and BEN2/VPS45 (Sec1/Munc 18 protein) function in intracellular trafficking of PIN proteins in Arabidopsis. Mutations in both BEN1 and BEN2 resulted in defects in polar PIN localization, auxin response gradients, and in root architecture. In this study, we have attempted to gain insight into the developmental roles of these trafficking components. We showed that while genetic or pharmacological disturbances of auxin distribution reduced dividing cells in the root tips and resulted in reduced root growth, the same manipulations had only moderate impact on ben1; ben2 double mutants. In addition, we established transgenic lines in which BEN2/VPS45 is expressed under control of tissue-specific promoters and demonstrated that BEN2/VPS45 regulates the intracellular traffic of PIN proteins in cell-autonomous manner, at least in stele and epidermal cells. Furthermore, BEN2/VPS45 rescued the root architecture defects when expressed in internal tissues of ben1; ben2 double mutants. These results corroborate the roles of the endosomal trafficking component BEN2/VPS45 in regulation of auxin-dependent developmental processes, and suggest that BEN2/VPS45 is required for sustainable root growth, most likely through regulation of tip-ward auxin transport through the internal tissues of root.